Merawat Impian Masa Depan Dalam Menghindari Pernikahan Dini Di Dusun Karangkamal Desa Margacinta - Ai Teti Wahyuni; Dede Asiah; Agun Gunawan; Muhammad Rifqi Al- As’ari (Jurnal Kabar Masyarakat, 2023)
Early marriage is a marriage that occurs at a very young age, usually under 18 years of age. Early marriage is often caused by economic, social, cultural and religious factors. The method of implementing service is carried out using the PAR (Participatory Action Research) method. This service was carried out by posyandu in Karangkamal Hamlet, Cijulang District, Pangandaran Regency in August 2023. The output target to be achieved is: the participation of all elements of society to reduce the rate of early marriage. This includes providing access to education and employment, making people aware of the negative impacts of early marriage, and strengthening the role of families in educating children so they understand the importance of healthy and responsible relationships. The conclusion is that teenagers and parents are very enthusiastic and welcome this activity. They hope that there will be good changes from this activity..